Project Based Learning Model Box Sifcay Assistance in Improving Science Learning Outcomes - I Made Gabriel Sirman; Widdy H.F. Rorimpandey; Susan N.H. Jacobus (Universitas Pendidikan Ganesha, 2025)
The lack of active involvement and in depth understanding of concepts causes the low learning outcomes of students in science subjects. Conventional learning methods are considered less able to stimulate critical thinking skills. This study examines the effectiveness of applying project based learning models with Box Safety Media to improve student learning outcomes in science subjects. This type of research uses Classroom Action Research (CAR) design; each cycle consists of four stages: planning, action, observation, and reflection. The total number of students is 33, consisting of 17 boys and 16 girls. The methods used in data collection are observation and testing. The research instrument is in the form of questionnaires and tests. Data analysis techniques use qualitative and quantitative descriptive analysis. The results show that using the Sifcay Assisted Project Based Learning improves the learning outcomes of fifth grade students. This can be seen from the learning outcomes of students who have increased from cycle I to cycle II, from 72.2% to 90.6%. It is concluded that the Box Sifcay Project Based Learning Assistance learning model can improve science learning outcomes in fifth grade students. The implication is that applying the Box Sifcay project based learning model can effectively improve students' science learning outcomes through more contextual and meaningful learning experiences.